Dietary Zinc and the brain. - Rahman, Mohammad Tariqur (Springer Science Business Media, 2011)
Zinc (Zn), after iron, is the second most abundant essential element in different organs of the human body. The amount of Zn to be absorbed and hence utilized or metabolized in different tissues depends on the total Zn content of the diet and its bioavailability, specially its solubility in the intestinal lumen. In the brain, additional control on the absorption, distribution, and homeostasis of Zn is maintained by the blood brain barrier system which generally is not easily disrupted by dietary Zn. In the brain, [Zn] is highest in the hippocampus but this can be decreased significantly in dietary Zn deficiency. Zinc homeostasis in the brain is maintained through the regulated expression of proteins for Zn import, export, and storage. Among them, Zn2+ transporters, Zn2+ importing proteins, and Zn2+ buffering proteins, such as the metallothioneins, bind cytosolic free Zn2+ and mediate the complex intraneuronal cytosolic Zn2+ homeostasis. In addition to its important roles as catalytic, co-catalytic, and structural component of many proteins, Zn is also important as an intracellular signaling factor in the regulation of cell proliferation. As an extracellular signaling factor, Zn is involved in synaptic neurotransmission. In neuronal cells, Zn deficiency induces oxidative stress, which consequently can induce decreased cell proliferation and increased apoptosis through activation and inactivation of several Zn finger transcription factors. Acute human dietary deficiency of Zn is associated with symptoms such as anorexia, smell and taste dysfunction, emotional and cognitive disturbances, and loss of coordination and other brain functions, including learning and memory defects. The intracellular Zn2+ availability is associated with decline in brain functions and impaired cognitive performances in old age. This chapter will elaborate on the physiological importance of dietary Zn in the brain with special reference to the mechanism of Zn homeostasis, the role of dietary Zn in brain development, and the consequences of an Zn excess and/or Zn deficient condition in brain pathology.